The analysis of pumpless cooling systems reciprocating compressors - E. A. Dorofeev; A. S. Tegzhanov; V. E. Shcherba (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses the existing methods of cooling reciprocating compressors, where special attention is paid to liquid systems in which the motion of the coolant is carried out not from an external pump, but due to fluctuations in gas pressure or rarefaction. An analysis of the designs of pumpless cooling systems is carried out, advantages and disadvantages are identified, directions for their further improvement are identified.